Petletni pravni študij in razvoj pravnega študija v svetu - Accetto, Matej (Pravnik, 2017)
The text deals with the idea of the reform of legal studies in the form of a unified five-year master's degree that has been developing over the past few years at the University of Ljubljana Faculty of Law. This contribution to the debate on such a reform briefly surveys the initiatives and the study reforms recently carried out around the world - in Europe, the US, Australia, India, South Africa, South Korea, Japan and elsewhere - and attempts to glean from them tools with which to evaluate and improve the initiative at the Ljubljana Faculty of Law. The survey paints the familiar image of great diversity among the study programmes that reflect the differences among the socially and politically conditioned legal systems, but it also shows a number of their similar features as well as similar goals of the reforms undertaken in the past few years, which seem to favour the organization of a unified degree programme in law.
Keywords: law; pravo; študij prava; študijski programi